Reviving Jyotismati an endangered medicinal plant - Das, Manish; Rana, V S (Indian Horticulture, 2019)
The Jyotismati (Celastrus paniculatus), a shrub is widely used in Ayurdevic medicine in India. Various properties are attributed to the aerial parts of the plant, but its seeds and seed oil are more generally used in Indian system of medicine. Its seeds and oil have long been regarded in India as beneficial to the intellect and memory. The seeds are hot, bitter, dry, and acrid in taste. It cures joint pain, rheumatism, and weakness. The seed oil enriches the blood, cures abdominal complaints, stomachic, tonic, treats cough, asthma, leprosy, headaches, leucoderma etc. Aqueous extracts of its seeds improves learning and memory in rats. In addition, these extracts have antioxidant properties, augmented endogenous antioxidant enzymes, and decrease lipid peroxidation in rat brain.